DETERMINANTS OF ECONOMIC EXPOSURE: AN EMPIRICAL EVIDENCE FROM THE MISCELLANEOUS COMPANIES IN INDONESIA - Majid, M. Shabri Abd.; Zainul, Zaida Rizqi; Sakir, A. (D-III Keuangan dan Perbankan, 2015)
This research empirically measures the economic exposure of 11 selected miscellaneous companies in Indonesia. It also attempts to empirically explore the influence of firm size, export, liquidity, and leverage on the economic exposure of those companies. Annual data from 2007 to 2010, which was collected from theÂ www.idx.co.id andÂ www.bi.go.id were used and analyzed by the multiple linear regression to measure the economic exposure and examine the influences of the firm size, export, liquidity, and leverage on the economic exposure. Both partial (t-test) and simultaneous (F-test) hypotheses were constructed and tested using the software of SPSS for Windows. The research documented that, with the exception of the liquidity, which has a negative and significant effect partially on the economic exposure, all other variables, i.e., the firm size, export, and leverage were found to have insignificant effects. Meanwhile, based on the F-test, the research found that the firm size, export, liquidity, and leverage affected simultaneously and significantly the economic exposure of the companies. These findings imply that in order to manage their economic exposure, the companies should control these variables, especially the liquidity.